Politeness Strategies for Men on WhatsApp Social Media - Yulandari Yulandari (Universitas Muhammadiyah Enrekang, 2022)
Men's politeness in social media is still often ignored. This article aims to describe male-language politeness strategies in group WA conversations. This research is descriptive qualitative. The population were all the speeches in the WA alumni/bachelor (GA) group and the class/student group (GK). Data collection in WA conversations was taken in August-September 2022. The data collection technique was by taking screenshots on the WA group. Then use the note-taking technique into MS Word. The data that has been collected is then coded based on Brown & Levinson's theory of politeness. The findings show that male conversational in GK tends to use blunt politeness strategies and positive politeness strategies. Whereas in GA, men tend to use positive politeness strategies and negative politeness strategies. This shows that the speech of men in GK tends to be less polite, especially if the interlocutor has close social distance with him. While in GA conversations, male speech tends to be more polite seen from the choice of using language politeness strategies. Men's utterances in GA conversations seem to rarely use frank politeness strategies even though their interlocutors have close social distances with them. This shows that the older a person is, the more careful they are in speaking. It is also inseparable from the educational factor. It is recommended that lecturers and other stakeholders to pay more attention to the politeness of the language of students, both male and female. By complying with the language politeness strategy, the relationship between the speaker and the speech partner will run harmoniously.Keywords: Gender, WhatsApp, Politeness Strategies, Education Level, Age.